Da Lapa aos porões da ditadura: as experiências de Raphael Martinelli (1939-1973) - Balbino, Ana Cristina Alves (2018)
The recent history of our country is formed by institutional violence and disregard for the rule of law. The experiences of those who have faced dictatorial impositions should be examples of the struggle for a better country. In this way, Raphael Martinelli's memoirs become important for the understanding of the period for this research, from 1939 to 1973. Trade unionism, especially in the Santos Jundiaí railroad, and the struggle against the civil-military dictatorship established after 1964, are examples of topics to be reflected and observed, so that we can review concepts and values today. This work attempts to trace a biography of political activist Raphael Martinelli, who has his life summarized in: a quick pass for youth football, the team of the São Paulo Athletic Club, current National Athletic Club, the experience of being a railroad in the São Paulo Railway, the presidency of the Railroad Workers' Union in São Paulo and the National Federation of Railroad Workers, head of the CGT, political persecution with the 1964 coup, participation in the National Liberation Action (ALN) and imprisonment in 1971, in Operation Bandeirante (Oban). The documentation used for this research is summarized in the biography “Iron Stations: Raphael Martinelli”; documents from your personal collection, such as police records, videos, interviews. To know the history of Martinelli is to get in touch with moments of political and social changes of our country. Its context of life is marked by four central points, that divided the chapters of this thesis: soccer, railroad, syndicalism and armed struggle. The themes are discussed from their experiences and memories. Through them we can see other possibilities, from a country that at the moment when it was learning to discuss democratic issues, such as the Basic Reforms, proposed by President João Goulart; and the relations between workers through their main representation, the union, suffered a heavy blow, with the seizure of power by the military, backed by civilian sectors, as wealthy landowners